Експериментальне дослідження точності прокатки на стані 800 - Зінченко, Михайло Дмитрович; Потап, Олег Юхимович; Бурчак, Андрій Анатолійович (Український державний університет науки і технологій, ННІ ≪Інститут промислових та бізнес технологій≫, ІВК ≪Системні технології≫, Дніпро, 2024)
UKR: Метою роботи є експериментальне дослідження процесу прокатки на стані 800 квадратних профілів для визначення впливу параметрів прокатки на розміри і довжину розкату. При дослідженні визначили коливання маси злитка, розмірів розкату, довжини розкату, отримали рівняння регресії і коефіцієнти кореляції залежностей розмірів та довжини розкату від маси злитка, змінення міжвалкового зазору і затримки часу перед чистовою кліттю. Встановлено, що коливання маси злитку відбувається в значних межах – 638 кг, що спричинено коливаннями маси плавки. Коливання маси злитка в межах одного піддона спричинено розмірами виливниць і знаходиться в межах 154 кг. Коливання розмірів розкату здійснюється в межах: товщина -1,0 мм, ширина – 0,5 мм, довжина – 5,3 м. Зміна міжвалкового зазору може бути використана для корекції довжини готового розкату в невеликому діапазоні довжин, якщо коливання маси відбуваються в межах точності розливу на одному піддоні. Необхідно додатково вживати заходів щодо стабілізації маси злитка. Вплив затримок у лінії стану, які виникають при прокатці і призводять до нестабільності температурного режиму прокатки, для даного типу профілів не позначається суттєво на розмірах поперечного перерізу і довжині розкату.

ENG: The study of fluctuations in the dimensions of rolled products was carried out for rolled profiles, which are a finished product, because fluctuations in the dimensions of the cross section and the length of the roll lead to the appearance of rods of excessive length when cutting on hot saws. Cutting the rolls does not always allow obtaining a mass of the blank, from which only rods of a measured length will be obtained in the next division. Therefore, increasing the accuracy of mass of square or round blanks allows to reduce fluctuations in the roll length and the appearance of rods of off-gage length and prevent the appearance of short blanks. The purpose of the work is an experimental study of the process of rolling on the state of 800 square profiles to determine the influence of rolling parameters on the dimensions of the cross-section and the length of the roll. During the study, fluctuations in ingot mass, rolling dimensions, and rolling length were determined, regression equations and correlation coefficients were obtained for the dependence of rolling dimensions and length on ingot mass, changes in interroll gap and time delay before the finishing stand. It was established that the mass of the ingot fluctuates within significant limits -638 kg, which is caused by fluctuations in the mass of the melt. Fluctuations in the mass of the ingot within one molding bed are caused by the dimensions of the ingot molds, the pouring height and is within 154 kg. Fluctuations in the dimensions of the roll are carried out within the following limits: thickness -1.0 mm, width -0.5 mm, length -5.3 m. Changing the interroll gap can be used to correct the length of the finished roll in a small range of lengths, if the mass fluctuations occur within accuracy of filling on one molding bed. It is necessary to take additional measures to stabilize the weight of the ingot. The influence of delays in the state line, which occur during rolling and lead to instability of the rolling temperature regime, for this type of profiles does not significantly affect the dimensions of the cross section and the length of the roll.
Experimental Study of Rolling Accuracy on Stand 800
М. Зінченко: ORCID 0000-0003-4381-9692; О. Потап: ORCID 0000-0001-8643-0228; А. Бурчак: ORCID 0009-0009-1075-888X
Keywords: маса злитку; товщина та ширина розкату; довжина розкату; струм двигуна; міжвалковий зазор; ingot mass; roll thickness and width; roll length; engine voltage; interroll gap; КАВП; TECHNOLOGY